IKHWANUL MUSLIMIN DAN GERAKAN TARBIYAH DI BANTEN DAN KOTA BATAM - Ahsanul Khalikin (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2012)
The presence of Ikhwanul Muslimin (IM) religious movement in one side creates a problem for the local religious organizations that have long existed, while on the other hand is seen as a movement that could give a new hope for the future of the Muslims of Indonesia. This paper explains how IM does forming a network and use it to deal with local religious (Islamic organizations) problem and its West challenge. To answer it, this study focuses on: (1) IM intellectual network and its tarbiyah movement, and (2) the institution network. The student intellectual network in Banten who has the thought and ideological movement of IM could be identified with the various activities in LDK “Ummul Fikroh” KBM Sultan Maulana Hasanudin IAIN Banten and Banten Tirtayasa University. While the thought and ideological movement of IM in Batam could be known through the teachers in SDIT Ulil Albab - Batam, the board of LDK Politiknik Batam and Raja Ali Haji Maritime University. Institutional linkage between ROHIS (schools), LDK and KAMMI (campus) and Partai Keadilan Sejahtera (PKS) are the issues of ideas and thoughts as well as the spirit. What is transcribed from IM thought is the spirit characteristic of the youth of Muslim, so that it could be easily absorbed by the students.